The fracture properties of metal‐ceramic composites manufactured via stereolithography. Issue 2 (6th December 2019) - Mummareddy, Bhargavi; Maravola, Michael; MacDonald, Eric; Walker, Jason; Hetzel, Brian; Conner, Brett; Cortes, Pedro
Abstract: In this work, metal‐ceramic composite parts based on aluminum and alumina were manufactured in a two‐stage process. First, silica was printed using a vat photopolymerization technique, followed by a curing and sintering stage, which resulted in ceramic precursors. Subsequently, these samples were subjected to a metal infiltration process to form interpenetrating metal‐ceramic composites (IPCs). These composites have attracted considerable attention in the aerospace and defense sector due to the ductility associated to the metal phase and the strength offered by the ceramics. A novel application with utility includes composite tooling which requires a low coefficient of thermal expansion (CTE) for high temperatures. The investigated specimens were tested for surface quality and shrinkage, followed by a mechanical characterization. It was recorded that the samples presented a 12%–18% of shrinkage after the sintering process. The mechanical testing showed that the hardness, compression, and flexural strength of the composites were superior to the printed and sintered ceramics. A thermal analysis on the composite showed that its CTE is more than two times lower than the common composite tooling materials. It is expected that the present work can provide the foundations for further studies on these systems in the refractory, automotive, and armor‐based fields.